Antimicrobial resistance in a One Health context: exploring complexities, seeking solutions, and communicating risks. Issue 1 (29th March 2019) - Scott, H. Morgan; Acuff, Gary; Bergeron, Gilles; Bourassa, Megan W.; Simjee, Shabbir; Singer, Randall S.
Abstract: Four articles presented in this special issue of Annals of the New York Academy of Sciences stem from a meeting of experts on antimicrobial resistance (AMR) in food animal production hosted by the New York Academy of Sciences on May 8 and 9, 2018. The articles discuss (1) competing considerations of the criticality of different classes of antimicrobials used for human and animal health and how guidelines and regulations might result in more prudent patterns of use; (2) the increasingly recognized importance of the environment (i.e., soil, water, and air) as a reservoir of resistant bacteria and resistance genes as well as a pathway for the dissemination of AMR between human and animal host populations; (3) established and novel solutions for measuring and containing the AMR problem; and (4) effective strategies for communicating to consumers the risks of AMR spreading from food production and other nonhuman sources. The authors of this commentary served as the scientific advisory committee to the meeting.